Financial sustainability of Islamic saving, credit cooperative society (SACCOS) in Tanzania - Said, Mariam Swalehe; Annuar, Hairul Azlan; Hamdan, Hamdino (2018)
The primary objective of this paper was to assess the financial sustainability of Islamic SACCOS in the Tanzanian context. Hence, to determine a five-year financial trend and factors affecting Islamic SACCOS financial sustainability. The dataset used in this study comes from four SACCOS audited financial reports from the year 2010 to 2014 as well as from interviews with SACCOS’s management. The study found that the IMFIs in Tanzania are not financially sustainable. Additionally, having responsible staff members, regular review of financial guidelines, staff training, and education to members are found to be highly contributing factors towards SACCOS's financial sustainability. Moreover, the findings reveal that depending on the single source of income, i.e., charges on members contributed much in these SACCOS’s not being financially sustainable. Based on these findings, the authors recommend that Islamic SACCOS needs to initiate productive projects that can enable them to have other income sources apart from charges on members.